The taxonomic status of Hyla pulchella joaquini (Anura : Hylidae) with description of its tadpole and vocalization - Garcia, PCA; Vinciprova, G.; Haddad, CFB (Herpetologists League, 2003)
We redescribe Hyla pulchella joaquini and describe its tadpole and vocalization. The taxonomic status of this subspecies is reevaluated; and on the basis of morphology, geographic distribution, and vocalization, we propose the elevation of this subspecies to specific level with the name Hyla joaquini B. Lutz 1968. We also discuss the relationship of H, joaquini within the species groups of H. pulchella Dumeril and Bibron 1841 and H. circumdata (Cope 1871).
Keywords: Anura; Hyla circumdata group; Hyla joaquini new combination; Hyla pulchella group; Hyla pulchella joaquini; tadpole; taxonomy; vocalization